2022
DOI: 10.5604/01.3001.0015.8384
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of modified Glasgow-Imrie, Ranson, and Apache II scoring systems in predicting the severity of acute pancreatitis

Abstract: <b>Aim:</b> The course of acute pancreatitis is variable with patients at risk of poor outcomes. The purpose of this study was to compare Modified Glasgow-Imrie, Ranson, and APACHE II scoring systems in predicting the severity of acute pancreatitis. </br></br> <b> Material and Methods: </b> After a brief history, clinical examination and qualifying inclusion criteria, 70 patients (41 women, 29 men) diagnosed with acute pancreatitis were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…The area of BISAP score under the ROC curve also considered as excellent for prediction of increased length of hospital stay, goodfor prediction of partial recovery withcomplication and moderatefor prediction of ICU transfer when cutoff values e"3 was taken as criteria for severe acute pancreatitis. These findings are parallel with other studies 16,17,18 . Chen et al 19 recommended that BISAP has the advantages of simplicity and speed over traditional scoring systems.…”
Section: Discussionsupporting
confidence: 92%
“…The area of BISAP score under the ROC curve also considered as excellent for prediction of increased length of hospital stay, goodfor prediction of partial recovery withcomplication and moderatefor prediction of ICU transfer when cutoff values e"3 was taken as criteria for severe acute pancreatitis. These findings are parallel with other studies 16,17,18 . Chen et al 19 recommended that BISAP has the advantages of simplicity and speed over traditional scoring systems.…”
Section: Discussionsupporting
confidence: 92%
“…As early as 1974,s using CMap, and the results indicated that the expression profiles of drugs-perturbed such as Entecavir, KU-0063794, Y-27632, and Antipyrine were significantly negatively correlated with the expression profiles of disease-perturbed, suggesting that these drugs can improve or even stop SAP progress 8 . Subsequently, numerous scoring systems based on clinical, imaging, and laboratory indicators, such as Glasgow 9 , APACHE II 10 , APACHE II 11 , APACHE II 12 , were developed to evaluate AP severity. While existing scoring systems have played a significant role in predicting sustained organ failure in AP, they have limitations, such as requiring multiple statistical parameters, being computationally complex, having a broad time span for required indicators, and exhibiting some lag in assessing disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…As early as 1974,s using CMap,and the results indicated that the expression pro les of drugs-perturbed such as Entecavir, KU-0063794, Y-27632, and Antipyrine were signi cantly negatively correlated with the expression pro les of disease-perturbed, suggesting that these drugs can improve or even stop SAP progress [8].Subsequently, numerous scoring systems based on clinical, imaging, and laboratory indicators, such as Glasgow [9], APACHE II [10], APACHE II [11], APACHE II [12], were developed to evaluate AP severity. While existing scoring systems have played a signi cant role in predicting sustained organ failure in AP, they have limitations,such as requiring multiple statistical parameters, being computationally complex, having a broad time span for required indicators, and exhibiting some lag in assessing disease severity.…”
Section: Discussionmentioning
confidence: 99%